Bilgi kaynaklarının yönetimi - Divarcı, Ulaş (My University, 2000)
Günümüzün iş dünyası korkunç bir değişim içinde rekabeti kaçınılmaz kılmaktadır. Rekabet olgusu sanayi toplumundan bilgi toplumuna geçtiğimiz son yıllarda bir çok yeni anlamlar ve boyutlar kazanmıştır. Geçmişin hammaddeye ve paraya dayalı rekabet stratejileri önce insan kaynağına günümüzde de bilgiye odaklanmıştır. Piyasalar hızla değiştiğinde, teknolojiler çoğaldığında ve ürünler çok kısa bir sürede eskidiğinde başarıyı sürekli kılan firmalar istikrarlı bir biçimde yeni bilgi yaratan, bu bilgiyi kuruluşun her yerine geniş ölçüde yayan, yeni teknoloji ve ürünleri hızla kullanan firmalardır. Konu hayalgücü ve yeni ürünler yaratmak olunca da bilgi birikimi büyük önem taşımaktadır. Zira çalışanın deneyimiyle oluşturduğu bilgi birikimi son derece kişiye bağlı ve transferi zor bir kaynaktır. Bu bilgi birikiminin kayıt altına alınması ve kuruluşta kullanılabilir özellikle de başkaları tarafından kullanılabilir bir hale getirilmesi rekabette önemli avantajlar sağlamaktadır. Bunun için rekabette avantaj sağlayacak bu bilginin bir organizasyonda eğer yoksa üretilmesi, varsa nerede olduğunun tanımlanması, onun organizasyona fayda sağlayacak şekilde kullanımının ve diğer çalışanlara kendi işlerinde kullanmaları amacıyla aktarımının sağlanması ve sonra da bu bilgiyi saklanması günümüz iş dünyası için kaçınılmaz bir zorunluluk olarak ortaya çıkmaktadır. Bir organizasyondaki bilgiyi ortaya çıkarmak ve bunu yönetmek yönetimlerin önemli fonksiyonlarından biri olarak ortaya çıkmıştır. Ülkemizde özellikle son yıllarda Yönetim Bilişim Sistemleri ile ilgili çalışmaların yoğunlaşmasına karşın bu çalışmalar bilgisayara dayalı raporlama sistemleri ve entegre üretim ve yönetim sistemleri kurma çalışmaları ile sınırlı kalmıştır. Yani bu çalışmalar su üstündeki bilgileri daha etkin biçimde paylaşılmasına odaklanmıştır. Oysa temel sorun paylaşım kadar mevcut bilginin su yüzüne çıkarılmasıdır. Çoğu kez aslında kuruluşta var olan bilgiyi oluşturmak için ikinci kez çaba harcanmaktadır. Bu da maliyetleri artırıcı ve rekabette geri kalınmasına yol açan bir durumdur. Özellikle literatürde var olan örtülü bilginin açık bilgiye dönüştürülmesi ve bunların toplanmasına yönelik yeterli bilgi ve uygulama bulunmamaktadır.

Today's business world, does the rivalry indispensable in a great process of change. The word rivalry has gained a lot of new meanings and dimensions in recent years in which we pass from industrial society to information society. The rivalry strategies of the past, which based on raw materials and money firstly focused on human resource then today to do information. When the markets rapidly change technologies develop, and the products are warn out in a short time; the forms that create information continuously, extend this information to every section of the firm widely and make use of new technologies and products will make the success continuous. Since the subject is imagination and creating new products, information accumulation carries a great importance for the information accumulation that the employee creates with this experience is a resource that is very personal and difficult to transfer. To register this information accumulation and provide its usage -especially by others- brings considerable advantages in rivalry. For this reason it is on indispensable obligation for today's business world to produce this information in an organization, which will create advantage in rivalry, if it is not produced yet; if it is produced, to describe its place, provide its usage for the benefit of organization and its transfer to the employees to use it in their own studies. To bring knowledge in an organization into light and manage it is seen as one of the most important functions pf management Although in our country the studies on management and Data Processing system condensed recently these studies were restricted into computer-based report systems and studies on establishing integrated production and management system. This means, these studies are focused on sharing out the surface information more eff4ectively. But the basic problem is not only the sharing but to make use of the available information. Most of the time, to create the information that is in fact already available in the institution, a second effort is spent. This increases the cost and lead to regress in rivalry. These are no adequate information and application especially on the information of covered information available in the literature into uncovered information and accumulation of them. In the light of this evaluation, in my study, the concepts on the description on of the organizational knowledge, which is the first, end the most important level of the knowledge management. Transformation carried out in organizations, knowledge maps from available knowledge, yellow papers and index techniques are examined in details. After the concepts about knowledge and knowledge management transformation are explained. In terns of it the techniques for the employees to reach the knowledge they want are explained in details. Also application of a method to describe covered knowledge in the institutions to determine the ways for defining it as the uncovered by the examples and by on application carried out in KalDer, which is a non-governmental organization.
Keywords: BİLGİ KAYNAKLARI YÖNETİMİ; Genel yönetim; Organizasyon ve finansman